2018
DOI: 10.1111/apa.14421
|View full text |Cite
|
Sign up to set email alerts
|

Using high‐flow nasal cannulas for infants with bronchiolitis admitted to paediatric wards is safe and feasible

Abstract: We found preliminary evidence that oxygen support needs and heart rate were useful early predictors of HFNC therapy success in infants hospitalised with bronchiolitis, but respiratory rate was not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
0
19
0
2
Order By: Relevance
“…A prospective study of infants with bronchiolitis examined HFNC initiation in the emergency department followed by ward admission, and identified non‐responders demonstrating no change in heart rate (HR) or respiratory rate (RR) in the first 60 min of initiation . Other studies have documented predictors of HFNC failure such as high oxygen requirement, history of intubation, cardiac comorbidity, and decreased HR but not RR …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective study of infants with bronchiolitis examined HFNC initiation in the emergency department followed by ward admission, and identified non‐responders demonstrating no change in heart rate (HR) or respiratory rate (RR) in the first 60 min of initiation . Other studies have documented predictors of HFNC failure such as high oxygen requirement, history of intubation, cardiac comorbidity, and decreased HR but not RR …”
mentioning
confidence: 99%
“…4 Other studies have documented predictors of HFNC failure such as high oxygen requirement, history of intubation, cardiac comorbidity, 5 and decreased HR but not RR. 6 Recently, two large randomized controlled trials (RCT) examined the effects of HFNC on children with bronchiolitis requiring supplemental oxygen. 7,8 The first RCT reported that although HFNC decreased the need to escalate care, it did not decrease the rate of PICU admission or duration of oxygen therapy or hospital stay.…”
mentioning
confidence: 99%
“…Infants and toddlers with bronchiolitis develop increased work of breathing to preserve oxygenation and ventilation in the setting of altered airway resistance and lung compliance. 2,3 In addition to oxygen supplementation, HFNC is used to reduce work of breathing through several mechanisms: [2][3][4][5][6] (1) Nasopharyngeal dead space washout clears oxygen-depleted gas at the end of expiration, facilitating alveolar ventilation (ie, carbon dioxide retention improves); (2) High flow rates match increased inspiratory flow demands of acutely ill patients, reducing nasopharyngeal inspiratory resistance and optimizing dead space washout, thus decreasing work of breathing; (3) Adequate flow rates generate distending pressure, which prevents pharyngeal collapse, supports lung recruitment, and reduces respiratory effort (demonstrated in younger infants); and (4) HFNC systems heat and humidify the breathing gas, reducing the metabolic work required to condition cool, dry gas and improving conductance and pulmonary compliance. [2][3][4][5] HFNC therapy is used more commonly in acute care units despite limited literature on its effectiveness outside the intensive care unit (ICU).…”
Section: Overview and Clinical Questionmentioning
confidence: 99%
“…The authors highlight the risk that infants treated with HHLFNC may be kept in oxygen therapy longer than necessary, because parents and nurses experience this treatment modality so comfor- 1,4 We agree that such protocols for weaning off oxygen therapy should be available and in active use in all hospitals treating infants with bronchiolitis.…”
mentioning
confidence: 97%